Food design: from reflection to formulation process - Ramírez-Navas, Juan Sebastián; Betancourt-Botero, Sandra Patricia; Montoya-Devia, Leidy Marcela; López-Ramírez, María Patricia (Revista Colombiana de Investigaciones Agroindustriales, 2024)
In this paper, a reflection exercise is presented, which stems from the analysis of the work carried out over several years by the team of researchers in the Food Science and Technology field, leading to the structuring of an innovative educational protocol focused on food design through Challenge-Based Learning (CBL), Project-Based Learning (PBL), and Design Thinking (DT). Each part of the protocol is detailed along with its grounding in scientific literature. The importance of properly structuring a diverse and cohesive team, carefully selecting the target market, and formulating and prototyping based on real consumer needs was highlighted. This pedagogical methodology not only aims to innovate in the food industry but also prepares students to face real challenges, promoting competencies such as leadership, critical thinking, and practical skills, integrating technical and practical knowledge, seeking future professionals who contribute significantly to the food industry and public health improvement.